Township-level governance in disaster preparedness in Yangon, Myanmar, during the period of transformation from April 2011 to January 2021 - Zin Mar Than; Hlaing Maw Oo; Sophie-Bo Heinkel; Toe Aung; Tin Tin Kyi; Saw Sandar Oo; Win Lei Mar; Win Maung; Zin Nwe Myint; Khin Khin Soe; Marlene Willkomm; Christian Miller; et al. (Natural Hazards, 2026)
Since Cyclone Nargis hit the country in 2008, Myanmar has stepped up its efforts to implement a disaster management system aimed at reducing disaster risk. At the same time, a far-reaching political and social transformation took place, shifting from military to civilian administration between April 2011 and January 2021. During this period, new concepts for disaster risk management were developed internationally, focusing on local governance and community-based strategies. This article provides an overview of the legal and organisational framework introduced in Myanmar for disaster risk management during the transition phase. In particular, it examines how and to what extent governance elements have been integrated into the system to meet local societal needs. The focus is on identifying challenges, gaps and opportunities in local governance structures. The study employs a mixed-methods analysis approach. This involved conducting 28 expert interviews with Yangon-based disaster management institution members as well as a quantitative household survey of 896 people in eight Yangon townships. Additionally, an in-depth analysis of government documents and reports was conducted. The study shows that the general framework for implementing governance aspects was already well established when the political system changed again in 2021. In practice, however, governance aspects remain challenging.

Genetic diversity and phylogenetic relationships among western and Asian honey bees, and Eristalis tenax collected in Myanmar - Saw Bawm; Aye Pyae Pyae Khaing; Hlaing Min Oo; Myint Myint Mu; Ngwe Chi Hmuu; Aye Nyein Sandi Zaw; Nyunt Lwin; Hla Myet Chel; Yadanar Khaing; Shwe Yee Win; Lat Lat Htun; Shiro Murata; et al. (Journal of Asia-Pacific Entomology, 2025)

Early Carboniferous Magmatic Rocks in Eastern Myanmar: Implications for the Tethyan Evolution - San Win; Qinglai Feng; Ye Myint Swe; Tianyu Zhao; Zhengqin Gan; Xiaomei Nie; Aung Khaing; Sai Naing Lin Aung (Journal of Earth Science, 2025)

Epidemiological and clinical profile of snake envenomation in children and adolescents admitted to tertiary hospitals in Yangon, Myanmar - Khin Than Yee; Kyaw Zin Wai; Aung Pyae Phyo; Lai Lai San; Khin Moe Latt; Tin Tin Htike; Thet Htet Aung; Aung Myat; Han Win; Zaw Myint; Zaw Than Htun (Toxicon, 2024)

How context affects transdisciplinary research: insights from Asia, Africa and Latin America - Flurina Schneider; Aymara Llanque-Zonta; Onintsoa Ravaka Andriamihaja; R. Ntsiva N. Andriatsitohaina; Aung Myin Tun; Kiteme Boniface; Johanna Jacobi; Enrico Celio; Clara Léonie Diebold; Laby Patrick; Phokham Latthachack; Jorge Claudio Llopis; et al. (Sustainability Science, 2022)
Transdisciplinary research (TDR) has been developed to generate knowledge that effectively fosters the capabilities of various societal actors to realize sustainability transformations. The development of TDR theories, principles, and methods has been largely governed by researchers from the global North and has reflected their contextual conditions. To enable more context-sensitive TDR framing, we sought to identify which contextual characteristics affect the design and implementation of TDR in six case studies in Asia, Latin America, and Africa, and what this means for TDR as a scientific approach. To this end, we distinguished four TDR process elements and identified several associated context dimensions that appeared to influence them. Our analysis showed that contextual characteristics prevalent in many Southern research sites—such as highly volatile socio-political situations and relatively weak support infrastructure—can make TDR a challenging endeavour. However, we also observed a high degree of variation in the contextual characteristics of our sites in the global South, including regarding group deliberation, research freedom, and dominant perceptions of the appropriate relationship between science, society, and policy. We argue that TDR in these contexts requires pragmatic adaptations as well as more fundamental reflection on underlying epistemological concepts around what it means to conduct “good science”, as certain contextual characteristics may influence core epistemological values of TDR.

Disaster preparedness and resilience at household level in Yangon, Myanmar - Sophie-Bo Heinkel; Benni Thiebes; Zin Mar Than; Toe Aung; Tin Tin Kyi; Win Lei Mar; Saw Sandar Oo; Christian Miller; Marlene Willkomm; Win Maung; Zin Nwe Myint; Khin Khin Soe; et al. (Natural Hazards, 2022)
Resilience has become important in disaster preparedness and response. Unfortunately, little is known about resilience at the household level. This study presents the results of a survey into individual and household level preparedness to disaster events in Yangon, Myanmar, which is prone to natural disasters such as tropical cyclones, flooding, and earthquakes. The study aimed to understand societal resilience and to provide information that could be used to develop a holistic framework. In four different Yangon townships, 440 households were interviewed. The results of the survey indicate how risk preparedness could be improved by specific measures related to the following five factors: (1) increasing the general public’s knowledge of first aid and its role in preparedness; (2) improving mobile phone infrastructure and capacity building in its usage so that it can be used for communication during disasters, along with building up a redundant communication structure; (3) better use and organisation of volunteer potential; (4) more specific involvement of religious and public buildings for disaster response; and (5) developing specific measures for improving preparedness in urban areas, where the population often has reduced capacities for coping with food supply insufficiencies due to the high and immediate availability of food, shops and goods in regular times. The findings of this survey have led to specific recommendations for Yangon. The identified measures represent a first step in developing a more general framework. Future research could investigate the transferability of these measures to other areas and thus their suitability as a basis for a framework.

Anti-hepatitis B activities of Myanmar medicinal plants: a narrative review of current evidence - Ye Htut Linn; Win Win Ei; Lwin Mon Mon Myint; Khin Maung Lwin (VirusDisease, 2021)

Microscopic and molecular detection of Eimeria maxima and Eimeria praecox naturally infected in free-range village chickens of Myanmar - Saw Bawm; Shwe Yee Win; Nyein Chan Soe; Yu Nandi Thaw; Myint Myint Hmoon; Lat Lat Htun; Ryo Nakao; Ken Katakura (Acta Parasitologica, 2021)

Population structure of Nga Myin Yinn Silonia silondia in the Ayeyarwady River, Myanmar, by mitochondrial DNA markers - Toe Toe Soe; Thida Lay Thwe; Pwint Thu Aye; Kyi Thar Myint; Than Than Lwin; Ye Win Thaung; Aye Aye Min; Shota Mitsui; Takeshi Terahara; Masato Endo; Masashi Yokota; M. Moshiur Rahman; et al. (Fisheries Science, 2021)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Laboratory investigation on the compressibility of Singapore marine clays - Myint Win Bo; Victor Choa; Jian Chu; Arul Arulrajah; Suksun Horpibulsuk (Marine Georesources & Geotechnology, 2017)

Seasonal dynamics influencing coastal primary production and phytoplankton communities along the southern Myanmar coast - Maung-Saw-Htoo-Thaw; Shizuka Ohara; Kazumi Matsuoka; Tatsuya Yurimoto; Shota Higo; Khin-Ko-Lay; Win-Kyaing; Myint-Shwe; Sein-Thaung; Yin-Yin-Htay; Nang-Mya-Han; Khin-Maung-Cho; et al. (Journal of Oceanography, 2017)

Mineralogy and Geotechnical Properties of Ultrasoft Soil from a Nearshore Mine Tailings Sedimentation Pond - Myint Win Bo; Arul Arulrajah; Patimapon Sukmak; Suksun Horpibulsuk; Melvyn Leong (Marine Georesources & Geotechnology, 2016)

Step Loading Compression of Ultra-Soft Soil under Radial Drainage Conditions - Myint Win Bo; Kai Sin Wong; Victor Choa; Arul Arulrajah; Suksun Horpibulsuk (Marine Georesources & Geotechnology, 2016)

Ground Investigations for Changi East Reclamation Projects - Myint Win Bo; Ming-Fang Chang; A. Arulrajah; Victor Choa (Geotechnical and Geological Engineering, 2012)

Laboratory Validation of Ultra-Soft Soil Deformation Model - Myint Win Bo; Victor Choa; Kai Sin Wong; Arul Arulrajah (Geotechnical and Geological Engineering, 2011)